Evaluasi dan Pemetaan Tingkat Kerusakan Jalan di Kelurahan Kadumerak, Kecamatan Karang Tanjung, Kabupaten Pandeglang - Devyan Meisnnehr; Heriansyah Putra; Triyogo Aleksandria; Muhammad Adhiragil Kandyas; Fazrina Andriani Sakinah Lubis; Fikha Raihani; Nurul Chairunnisa; Giri Rasyidpradana Ganda; Shahilla Larasaty; Risma Amelia (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The road will decrease the level of service over time. The decreasing level of road services will be marked by damage to the road. Damage that occurs also varies in each segment along the road. Therefore, an evaluation of the extent of road damage is needed. Evaluation results can be presented in map form. Mapping the level of road damage is done by comparing two methods, namely the DGH method and the Geographic Information System (GIS) method. The results of the study show that most of the Kelurahan Kadumerak roads have a mild level of damage. The total length of the road with the level of severe damage is 0.31 km or equivalent to 2.25% of all roads in Kadumerak Village. The road is an asphalt road with pavement conditions which are full of damage in the form of road holes. The road is located in Lebak Seureuh village. On the other hand, a non-pavement road in Kadumerak Village has a total length of 1.19 km. We recommend that the roads in Cipapais Hilir and Kampung Kota Manik be included in the kelurahan development program. Further surveys need to be done to re-measure the dimensions of the road that will be repaired more accurately. Keywords: Bina Marga method, road damage, road mapping